Differences between cattle and buffalo in the water-soluble proteins of the Longissimus muscle as shown by electrophoretic techniques - Pinheiro, Rafael S. B. [UNESP]; Ramos, Paulo R. R. [UNESP]; De O. Roça, Roberto [UNESP]; Bezerra, Leilson R.; Francisco, Caroline L. [UNESP]; Oliveira, Ronaldo L. (CSIRO Publishing, 2020)
Context: Fraudulent information about food is an old and widespread problem, particularly regarding products with high economic value, such as meat and meat products. The motivation for food fraud is economic, but it can have serious impacts on public health, thus creating a food security problem. Approximately 90% of buffalo meat is marketed as beef in various regions where the consumption of buffalo meat is considered unusual. Aims: To determine the electrophoretic profile of the raw Longissimus dorsi of cattle and buffalo species and to test the hypothesis that electrophoresis techniques can be used to distinguish meat from cattle from buffalo meat. Methods: Fourteen 10-g samples of Longissimus dorsi (12th and 13th rib) tissue were taken from each animal of both species after slaughter. The meat of each species was analysed by native polyacrylamide gel electrophoresis (NATIVE PAGE) and by denaturing and non-denaturing sodium dodecyl sulfate (SDS)-PAGE. Differences (P < 0.05) were observed between water-soluble cattle and buffalo muscle proteins in both NATIVE PAGE (relative mobilities and percentages of protein bands) and non-denaturing and denaturing SDS-PAGE (molecular weights in kDa and optical density index). Key results: With the NATIVE PAGE technique, 10 protein bands were observed in the gel, and three of these bands exhibited differences between species (P ≤ 0.05). The non-denaturing and denaturing SDS-PAGE techniques yielded significantly different protein bands in the gel. The electrophoretic profiles of some cattle and buffalo muscle proteins are distinct; therefore, raw meat flesh samples of these animal species can be distinguished using these electrophoresis techniques. Conclusions: Each of the three electrophoresis techniques used can distinguish meat from different animal species; however, when there is doubt about the animal species, the use of more than one electrophoretic technique is recommended, so as to obtain more reliable results. Implications: The use of electrophoresis techniques to differentiate cattle and buffalo meat is promising. This technique could be used in cases of suspected food fraud, such as the replacement of beef with buffalo or vice versa, with reliable results that will be accepted by supervisory bodies.
Keywords: adulteration; muscle biochemistry; myofibrillar proteins; protein bands; ruminants